Developing a Questionnaire on Measuring the Learning Motivation in Reading Quran - Yusuf Hanafi; Muhammad Saefi; M. Alifudin Ikhsan; Tsania Nur Diyana; Abd Rauf Hassan; Nurul Murtadho (Jurnal Pendidikan Islam, 2021)
Learning motivation has been examined for its positive influence on learning outcomes. However, little attention has been addressed to the development of measuring instruments of learning motivation in the context of reading the Quran in Indonesian higher education. This study was designed to develop a Quran learning motivation questionnaire. The Self-Determination Theory (SDT) was applied as a theoretical framework to explore the type dan level of motivation. Participants involved in this study were 420 students. They were divided into subsample one for exploratory factor analysis (N = 200) and subsample two with confirmatory factor analysis (N = 220). The questionnaire was developed with 12 item-three factors using five points Likert scale that can measure the learning motivation in reading Quran. The results of the study show that the level of student motivation is relatively low (M= 3.12), and the intrinsic motivation type (M= 3.99) is more dominant than extrinsic motivation survival (M= 2.99) and approval (M= 2.38) with a p-value of 0.000. In addition, it was found that female students (M= 3.19) had significantly higher motivation than male students (M= 3.04), with a p-value of 0.017.